Traditional Wrestling of Gagauz Turks And its Role in Strengthening of Nation's Cultural Traditions - Orhan Ahmet Şener; Mehmet Türkmen (Selcuk University, 2020)
This article is about one of the unique and rarest fragments of the cultural heritage of the Gagauz Turks people - national "Güreş" wrestling, information about which is partially preserved and has survived till nowadays. Published materials give information about national "Güreş" wrestling and its role in historical, cultural and socially significant processes of modern society development. Method: in the study conducted with observation and literature review, descriptive research method was used. While writing the article, authors came to the conclusion that the preservation, popularization and further development of traditional sports in Gagauzia contribute to the development of both national and modern sports in Gagauzia and out. It also will contribute to the unity of people based on the interest to know their national and ethnic roots, national and unique traditions and customs of other peoples, increase a sense of national dignity, social justice, patriotism and responsibility for the future of the country. Presented material is the result of expeditions and long-time scientific research in archives, first published outside of the Republic of Moldova. Such researches are relevant in the context of preserving the cultural heritage and supporting unique national development of not only Gagauz people, but also all small nations of the world.